2015
DOI: 10.1016/j.rser.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the extended energy efficiency gap-evidence from Swedish electricity-intensive industries

Abstract: Energy efficiency is one of the major means of reducing CO2 emissions resulting from industrial use of energy. Both from a societal as well as business perspective it is of great importance to reduce industrial energy end use (EEU). The implementation of energy-efficient technologies as well as increased focus on energy management practices has been stated by previous research to be the two most important methods of improved industrial energy efficiency. To date, however, there are few (if any) studies that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 21 publications
(43 reference statements)
2
33
0
Order By: Relevance
“…A policy intervention was crucially required to raise the growth rate of energy productivity, as was done by the government of India with the launching of the National Mission on Enhanced Energy Efficiency under the National Action Plan on Climate Change [68]. The government should establish policies and supporting schemes related to energy efficiency to minimize the existing barriers was declared by [3]. This is further emphasized by the European Energy Efficiency Directive, which has the aim of removing market barriers and imperfections [69].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A policy intervention was crucially required to raise the growth rate of energy productivity, as was done by the government of India with the launching of the National Mission on Enhanced Energy Efficiency under the National Action Plan on Climate Change [68]. The government should establish policies and supporting schemes related to energy efficiency to minimize the existing barriers was declared by [3]. This is further emphasized by the European Energy Efficiency Directive, which has the aim of removing market barriers and imperfections [69].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…For energy-intensive industries, it is known that energy costs may account for up to and over 30% of total production costs [3], so at the firm level, improving energy efficiency is intended to generate direct economic benefits by decreasing the amount of energy used in production [4,5]. This global industrial sector share consists of 42%, 75%, 44% and 20% of the global electricity generated, coal, natural gas, and oil consumption, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…Brunke et al [3], in their study of the Swedish iron-and steel industry, stated that the potential for management was about 2.4% of the total energy use, while that for technology was stated to be 7.3%. Following [1][2][3][4] empirically investigated more than 900 energy efficiency measures undertaken by 100 Swedish energy-intensive industrial companies showing that a large number of the adopted measures were not, in fact, technology implementations. This research challenges the existing view that (best-available) technology is the sole means by which improved energy efficiency is achieved in industry, and accentuates a knowledge gap in the way improved energy efficiency in general is viewed.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, EnM is still not fully implemented. Indeed, research has demonstrated the existence of an energy-efficiency gap-the difference between the EE that could be achieved theoretically and the actual EE [1]-and that some of this gap can be reduced by EnM practices ( [2,3]). Research also presents the means for minimizing this gap by summarizing and describing the methods and technology for making use of energy more efficiently.…”
Section: Introductionmentioning
confidence: 99%